Ethnomedicinal Practices by Tharu Ethnic Community in Rupandehi and Nawalparasi Districts, Western Nepal - Thapa, Chandra Bahadur (Journal of Institute of Science and Technology, 2020)
Tharus are the marginalized indigenous people of Nepal. This study was carried out using Participatory Rural Appraisal (PRA), Rapid Rural Appraisal (RRA), and Focus Group Discussion (FGD) from 2019 to 2020. The ethnomedicinal data were collected using a semi-structured interview with 75 key informants, local healers, and Guruwas. A total of 74 plants, belonging to 39 families, for the treatment of 11 categories of ailments, were documented. The highest informant consensus factor (FIC) value was for respiratory troubles (0.84), followed by the skeletomuscular disorder (0.83), and dermatological trouble (0.82). The highest frequency of citation (%) was found in Azadirachta indica (90 %), followed by Calotropis gigantea (67 %), Euphorbia antiquorum (67 %), and Rauvolfia serpentina (51 %). Fabaceae (6 spp.) was the most dominating family; herbs (47 %) the most frequently used life forms; leaves (32 %) the most frequently used plant part, and juice (30 %) being the most widely preferred mode of drug preparation. Different parts of the plant species were used for the treatment of more than one ailment using a different mode of drug preparation, and a single species was used to treat more than one ailments. The high average FIC value (0.72) showed that there was a higher agreement among the informants for the use against certain categories of ailments. Some plants like Rauvolfia serpentina, Piper longum, and Asparagus racemosus need a proper conservation strategy, as their population is decreasing in this area.